Mandatory Assignments and Learning Achievement in a Mathematics Service Class. Issue 2 (7th February 2023) - Holden, T.; Burazin, A.
Abstract : Homework completion and self-regulatory ability have both been extensively studied to examine their impact on learning achievement. Moreover, the reciprocal nature of how these two qualities affect one another is also an area of research. While evidence shows that voluntary completion of assigned homework predicts self-regulation in students, a natural question is whether this can be facilitated with mandatory homework assignments. Research to this extent has been tentative: results are often positive, but issues with experimental design preclude strong conclusions or repeatability of the experiment. This paper aims to quantify the effect of mandatory homework assignments on learning achievement at the tertiary level while improving on the experimental design of existing research.